Effect of constituents of the foliar wax of Didymopanax vinosum on the foraging activity of the leaf-cutting ant Atta sexdens rubropilosa - Salatino, Antonio; Sugayama, Regina L.; Negri, Giuseppina; Vilegas, Wagner [UNESP] (Wiley, 1998)
Leaf epicuticular waxes may affect substrate selection by leaf-cutting ants, and host recognition by several phytophagous insects. The influence of the crude epicuticular wax of Didymopanax vinosum E. March. (Araliaceae), and its major constituents lupeol and free primary alcohols, on substrate selection by the leaf-cutting ant Atta sexdens rubropilosa Forel, was investigated. Two ant colonies were used in laboratory bioassays. Corn flakes (zea) were impregnated with chloroform solutions of the substances being tested and fed to the adults. One of the colonies gave results, in most of the tests, not significantly different from the controls. The other colony, however, discriminated against the crude wax, a strong deterrent effect being observed from the first of a series of eight trials. The same colony was able to discriminate against lupeol after the second trial. The fraction of primary n-alcohols (22% C28, 66% C30 and 12% C32) deterred feeding only after the fifth trial. The results demonstrate that some constituents of epicuticular waxes may deter the foraging activity of A. sexdens rubropilosa, depending, however, on the colony under observation. It is suggested that lupeol, of the foliar wax of D. vinosum, is an important deterrent to leaf-cutting ants, although with less pronounced effects than those observed in tests with the crude wax.
Keywords: Cerrado; Araliaceae; Atta sexdens rubropilosa; Didymopanax vinosum; Epicuticular waxes; Feeding deterrency; Leaf-cutting ants; Lupeol; Primary fatty alcohols; feeding deterrent; foraging activity; leaf wax; leaf-cutting ant; Atta sexdens; Formicidae; Hymenoptera; Zea